ON USING VARIOUS MATHEMATICS INSTRUCTIONS VERSUS TRADITIONAL INSTRUCTION-AN ACTION RESEARCH - Alzabut, Jehad (Journal on Mathematics Education, 2017)
In this research, I provide an overview of potentially selected interactive mathematical instructions that help learners-educators identifying the most effective practices for teaching a course on differential equations. Based on my practical experience, positive and negative aspects of the used techniques are discussed. Immediate reactions on the disadvantages of the implementation of these different instructions have been successfully demonstrated throughout the practices. I conduct a survey in form of a questionnaire asking the learners about their opinions in this experience from which conclusion and recommendation are drawn and proposed to use in the process of teaching and learning next semesters.DOI: http://dx.doi.org/10.22342/jme.8.2.4139.133-144